Tahapan pengembangan koleksi di Perpustakaan Umum Daerah Kabupaten Sumenep pada masa pandemi - Masita Dewi Cahyani; Fitri Perdana (Faculty of Communication, Padjadjaran University, 2022)
The Covid-19 pandemic has impacted the collection development activities in the Regional Public Library of Sumenep Regency. The pandemic has allowed libraries to improve their collection development activities, which were not previously a priority. This study aims to describe the existing activities of the stages of developing the collection in the Sumenep Regional Public Library during the pandemic. The research method used was descriptive qualitative, with the research subject being a librarian of the Sumenep Regional Public Library. Data collection was obtained through observation, interviews, and a literature review. Study results found that firstly, community analysis was conducted by distributing questionnaires links through Instagram accounts and the official website. Second, the collection development policy needed to be formally and officially formulated. Third, collection selection was carried out with a conformarian understanding, which is a balance between quality and interest in books. At this stage, the selection was carried out based on the data results from the step previously. Fourth, the procurement of library materials was hampered during the pandemic due to budget cuts for procurement allocations and the provision of digital libraries. Fifth, weeding was carried out more efficiently and focused during the pandemic. The final stage was collection evaluation, and it was found that the Sumenep Public Library itself did not carry out routine evaluations of collection development. It found several obstacles, namely budget cuts due to being diverted to Covid-19 funds, lacking human resources in the IT field, and lacking a collection development policy formulation. In conclusion, the Sumenep Public Library still needs more collection development during the pandemic.